La proteins couple use of sequence-specific and non-specific binding modes to engage RNA substrates. Issue 2 (1st February 2021) - Bayfield, Mark A.; Vinayak, Jyotsna; Kerkhofs, Kyra; Mansouri-Noori, Farnaz
ABSTRACT: La shuttles between the nucleus and cytoplasm where it binds nascent RNA polymerase III (pol III) transcripts and mRNAs, respectively. La protects the 3ʹ end of pol III transcribed RNA precursors, such as pre-tRNAs, through the use of a well-characterized UUU-3ʹOH binding mode. La proteins are also RNA chaperones, and La-dependent RNA chaperone activity is hypothesized to promote pre-tRNA maturation and translation at cellular and viral internal ribosome entry sites via binding sites distinct from those used for UUU-3ʹOH recognition. Since the publication of La-UUU-3ʹOH co-crystal structures, biochemical and genetic experiments have expanded our understanding of how La proteins use UUU-3ʹOH-independent binding modes to make sequence-independent contacts that can increase affinity for ligands and promote RNA remodeling. Other recent work has also expanded our understanding of how La binds mRNAs through contacts to the poly(A) tail. In this review, we focus on advances in the study of La protein-RNA complex surfaces beyond the description of the La-UUU-3ʹOH binding mode. We highlight recent advances in the functions of expected canonical nucleic acid interaction surfaces, a heightened appreciation of disordered C-terminal regions, and the nature of sequence-independent RNA determinants in La-RNA target binding. We further discuss how these RNA binding modes may have relevance to the function of the La-related proteins.